2019
DOI: 10.1038/s41598-019-54763-1
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of event-related alpha rhythm during the time course of anticipation

Abstract: Anticipation is the ability to accurately predict future actions or events ahead of the act itself. When attempting to anticipate, researchers have identified that at least two broad sources of information are used: contextual information relating to the situation in question; and biological motion from postural cues. However, the neural correlates associated with the processing of these different sources of information across groups varying in expertise has yet to be examined empirically. We compared anticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Figure 3 Panels B and C illustrate this effect for two single-trial simulations where beliefs about the more likely hidden state (normal or change-up) are updated across timepoints within a single trial according to the precision of each informational source, resulting in different action selections. These simulations correspond closely with many empirical findings in the sport anticipation literature 32,37,41,42 . For instance, Runswick et al 40 , found participants relied heavily on game context information when the delivery of a cricket ball was occluded at an early stage, but increasingly employed kinematic cues for later occlusions, as the precision of the kinematic cues (e.g., bowler's action) increased (see also 41 ). )…”
Section: Principle 1 -'Both Contextual and Current Sensory Information Can Influence Anticipation Performance Directly But This Effect Issupporting
confidence: 87%
“…Figure 3 Panels B and C illustrate this effect for two single-trial simulations where beliefs about the more likely hidden state (normal or change-up) are updated across timepoints within a single trial according to the precision of each informational source, resulting in different action selections. These simulations correspond closely with many empirical findings in the sport anticipation literature 32,37,41,42 . For instance, Runswick et al 40 , found participants relied heavily on game context information when the delivery of a cricket ball was occluded at an early stage, but increasingly employed kinematic cues for later occlusions, as the precision of the kinematic cues (e.g., bowler's action) increased (see also 41 ). )…”
Section: Principle 1 -'Both Contextual and Current Sensory Information Can Influence Anticipation Performance Directly But This Effect Issupporting
confidence: 87%
“…Gredin et al (2020b) combined continuous electroencephalography (EEG) and selfreport measures to assess the cognitive load associated with soccer players' processing of contextual priors during the anticipation task. The EEG data suggested that explicitly provided contextual priors increased experts' cognitive load, perhaps due to the recruitment of additional attentional resources (Simonet et al, 2019). In contrast, the retrospective self-report data indicated a decrease in cognitive load when priors were provided.…”
Section: Task Loadmentioning
confidence: 85%
“…This is an important consideration for the sports anticipation literature that has investigated contextual priors and their importance in the anticipation process (Runswick, Roca, et al, 2020). The majority of this work has explicitly provided contextual priors or deliberately developed tasks that are embedded with reliable contextual information (Simonet et al, 2019), potentially up-weighting their importance in the anticipation process.…”
Section: Discussionmentioning
confidence: 99%